PELAKSANAAN PENGELOLAAN KEUANGAN PADA BAITUL MAAL WAT TAMWIL (BMT) BASMALAH ARRAFI’UL A’LAA PONTOANAK - Royyin Royyin; Bambang Genjik; Husni Syahrudin (Universitas Tanjungpura, 2022)
Baitul maal wat tamwil arrafi’ul a’laa is an Islamic financial institution that provides services to the community both in terms of deposits and loans. This research aims to find out the implementation of financial management at BMT Basmalah Arrafi’ul A’laa Pontianak. The research method used is a qualitative method with a descriptive approach. Data collection tools used in the from of observation, interview and analysis of documents. From the results of the research it is known that the financial management of BMT Basmalah Arrafi’ul A’laa in the form of financing and saving loans. It can be known that lancer assets in 2016 to 2018 have increased. It also affects fixed assets, current debt and capital which also increased.Keywords: Implementation of financial management, BMT basmalah arrafi’ul a’laa